MENGGANTUNGNYA RUU PERAMPASAN ASET DALAM TINDAK PIDANA: HAMBATAN POLITIK, YURIDIS, DAN SOSIAL - Apriani Asnaye (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2025)
Rancangan Undang-undang (RUU Perampasan Aset) has been proposed for more than a decade, yet it remains unenacted despite its high urgency in combating criminal activities, particularly corruption. This study aims to analyze the factors contributing to the prolonged delay in the enactment of the Asset Forfeiture Bill from political, juridical, and social perspectives by employing Roscoe Pound’s Social Interest Theory as its analytical framework. This research adopts a normative legal research method using statutory and conceptual approaches. The findings indicate that the main obstacles to the enactment of the Bill do not lie in the weakness of its normative substance, but rather in political resistance, regulatory fragmentation, and the lack of legal commitment to prioritizing public and social interests. From the perspective of Social Interest Theory, the suspension of the Asset Forfeiture Bill reflects the state’s failure to balance individual interests—particularly property rights with public interests in asset recovery and broader social interests such as justice, welfare, and public trust in the legal system. The continued delay undermines the function of law as a tool of social engineering and weakens the effectiveness of criminal law enforcement. Therefore, the enactment of the Asset Forfeiture Bill constitutes a normative necessity to restore social justice, strengthen asset recovery mechanisms, and enhance the overall effectiveness of crime control in Indonesia.